Propensity score-based analysis of long-term follow-up in patients supported with durable centrifugal left ventricular assist devices: the EUROMACS analysis. (19th April 2021) - Potapov, Evgenij V; Nersesian, Gaik; Lewin, Daniel; Özbaran, Mustafa; de By, Theo M M H; Stein, Julia; Pya, Yuri; Gummert, Jan; Ramjankhan, Faiz; Zembala, Michael O; Damman, Kevin; Carrel, Thierry; et al.
Abstract: : OBJECTIVES: The HeartWare HVAD (HW) and the HeartMate3 (HM3) are presently the most commonly used continuous-flow left ventricular assist devices worldwide. We compared the outcomes of patients supported with either of these 2 devices based on data from the EUROMACS (European Registry for Patients with Mechanical Circulatory Support). METHODS: A retrospective analysis of the survival and complications profile in propensity score-matched adult patients enrolled in the EUROMACS between 01 January 2016 and 01 September 2020 and supported with either an HW or HM3. Matching included demographic parameters, severity of cardiogenic shock and risk-modifying end-organ parameters that impact long-term survival. Survival on device and major postoperative adverse events were analysed. RESULTS: Following 1:1 propensity score matching, each group consisted of 361 patients. Patients were well balanced (<0.1 standardized mean difference). The median follow-up was similar in both groups [396 (interquartile range (IQR) 112–771) days for HW and 376 (IQR 100–816) days for HM3]. The 2-year survival was similar in both groups [HW: 61% 95% confidence interval (CI) (56–67%) vs HM3: 68% 95% CI (63–73%) (stratified hazard ratio for mortality: 1.13 95% CI (0.83–1.54), P = 0.435].The cumulative incidence for combined major adverse events and unexpected readmissions was similar in both groups [subdistribution hazard ratio (SHR) 1.0 (0.84–1.21), P = 0.96]. Patients in the HW group demonstrated a higher risk of device malfunction [SHR 2.44 (1.45–3.71), P < 0.001], neurological dysfunction [SHR 1.29 (1.02–1.61), P = 0.032] and intracranial bleeding [SHR 1.76 (1.13–2.70), P = 0.012]. CONCLUSIONS: Mid-term survival in both groups was similar in a propensity-matched analysis. The risk of device malfunction, neurological dysfunction and intracranial bleeding was significantly higher in HW patients.